Words of agricultural tools In the dialect of the tribes of Al-Abad Mountains in Al-Ardah Governorate - Allaghabi, Hussain Salem Jaber (Arts for Linguistic & Literary Studies, 2021)
In this research, the researcher talk about the agricultural In this research, the researcher talk about the agricultural implements in the dialects of the tribes of Al-Abadal Mountains that he was collecting them from the inhabitants of those tribes and wrote it down. Then he explained its meanings with examples from the dialect of the tribes' inhabitants. Then he revised meanings with its original roots in Arabic dictionaries and knowing its proximity and distance it to Al-Fusha in terms of its significance, as it came under its roots in Arabic dictionaries. This research consisted of an introduction, and a preamble that defines the Al-Abadal region in terms of geography, and two sections, the first: the words of agricultural tools for the plow, and the second: the words of agricultural tools for the non-plow, and a conclusion that summarizes the most important results of the research.